Accuracy of ctDNA-based minimal residual disease detection in predicting postoperative recurrence of breast cancer: a meta-analysis - You, Hang; He, JiuJiang; Tian, Tian (Frontiers in Oncology, 2026)
BackgroundDetection of circulating tumor DNA (ctDNA) has attracted growing attention for predicting postoperative breast cancer recurrence; however, the differences between the landmark and surveillance strategies remain unclear.MethodsWe systematically searched the PubMed, Cochrane Library, Embase, and Ovid MEDLINE databases for studies published up to April 17, 2025. Effect models were selected based on heterogeneity tests to pool diagnostic indicators, including sensitivity and specificity. Subgroup analyses were conducted according to molecular subtype, detection method, analytical strategy, and disease stage.ResultsA total of 17 studies were included in the analysis. The sensitivity and specificity of the landmark strategy were 0.40 (95% CI: 0.22–0.62) and 0.95 (95% CI: 0.81–0.99), respectively. For the surveillance strategy, sensitivity was 0.79 (95% CI: 0.71–0.85) and specificity was 0.98 (95% CI: 0.92–0.99). The surveillance strategy significantly improved sensitivity without a substantial loss of specificity. Among molecular subtypes, triple-negative breast cancer(TNBC) exhibited the best performance under the surveillance strategy. Whole-genome sequencing (WGS), droplet digital PCR (ddPCR), and whole-exome sequencing (WES) all demonstrated high sensitivity within the surveillance framework.ConclusionctDNA serves as a highly specific biomarker for predicting postoperative breast cancer recurrence. The surveillance strategy substantially improves its sensitivity; however, the current performance remains below the ideal threshold for clinical implementation. Future research should focus on refining detection strategies and technologies to achieve personalized recurrence risk stratification and guide therapeutic decision-making.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251056270.